Geospatial Analysis of Telehealth Patient Distances within a Student-Run Free Clinic - Karan Gowda; Krishi Korrapati; Olivia Griffith; Iswarya Vimalan Jeya; Romil Patel; Rahul Mikkilineni; Melissa Chen; Scot Hill (Journal of Student-Run Clinics, 2026)
Background: Telehealth services within SRFCs have been shown to be effective; however, no previous studies within SRFC research have utilized geospatial analysis to assess the reach of telehealth services. The aim of this cross-sectional study was to visually and numerically assess the reachof telemedicine services at the Interprofessional Community Clinic and contrast it with the reach of our in-person clinic.Methods: All unique patients seen for their first primary care clinic visit during 2023 and 2024 were classified as receiving care via telehealth or in-person. Google Maps was used to estimate the exact, average road mile distance at the most typical patient visit time of Thursday at 6:30pm for each year from the ICC to the patient’s home address. Using geospatial software, the clinic location and centroids of each unique zip code were geocoded. Next, using Illinois road data, the shortest paths were summarized from centroid to ICC and visual geographical spread was depicted.Results: In 2023, the ICC saw 69 unique patients - 16 utilized telehealth and 53 in-person. On average, those who utilized telehealth services lived 12.1 miles away from the clinic, while those who visited in-person lived 7.8 miles away. In 2024, the ICC saw 101 unique patients - 10 via telemedicine and 91 in-person. On average, those who utilized telehealth services lived 12 miles away from the clinic, while those who visited in-person lived 11.3 miles away. None of the differences were statistically significant.Conclusions: In 2023, patients seen by the telehealth service, on average, lived farther away from the ICC than the patient seen in person for their first visit. The farthest patient being in the telehealth group illustrates how SRFCs can use telehealth services to expand their reach to patients in need who may not be able to travel to the clinic.